Islamic Education Program Approach to Islamic Personality Development - Hidayat, Tatang; Rizal, Ahmad Syamsu; Fahrudin, Fahrudin; Istianah, Istianah (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2024)
The development of science and technology, on the other hand, raises new problems in the world of education in higher education, especially the behavior shown by students with the rampant consumption of alcohol, drugs, promiscuous behavior, and abortion, which is undeniable evidence of the negative impact of scientific and technological progress. This research aims to analyze the Islamic education program's approach towards Islamic personality development in Miftahul Khoir Student Boarding School Bandung. This research uses a descriptive qualitative approach. Data collection techniques were conducted by means of interviews, observations, and documentation studies. Based on the results of the study, the Islamic education program at PPM Miftahul Khoir has a distinctive feature by referencing four main concepts in designing Islamic education programs, namely first getting to know the basics of boarding school science. Second, Tafaqquh Fiddīn. Third, leadership and entrepreneurship. Fourth, adab and ethics. This concept makes the program at PPM Miftahul Khoir different from Islamic education programs in Salafi boarding schools in general and other student boarding schools. The Islamic education program at PPM Miftahul Khoir will support the implementation of the objectives of Islamic education at PPM Miftahul Khoir, because the program is made by the educational objectives it wants to achieve. The Islamic education program at PPM Miftahul Khoir is divided into two program scopes: the program listed in the syllabus and the non-syllabus program.